Chromogenic and Fluorogenic Probes for the Detection of Illicit Drugs. Issue 5 (28th May 2018) - Garrido, Eva; Pla, Luis; Lozano‐Torres, Beatriz; El Sayed, Sameh; Martínez‐Máñez, Ramón; Sancenón, Félix
Abstract: The consumption of illicit drugs has increased exponentially in recent years and has become a problem that worries both governments and international institutions. The rapid emergence of new compounds, their easy access, the low levels at which these substances are able to produce an effect, and their short time of permanence in the organism make it necessary to develop highly rapid, easy, sensitive, and selective methods for their detection. Currently, the most widely used methods for drug detection are based on techniques that require large measurement times, the use of sophisticated equipment, and qualified personnel. Chromo‐ and fluorogenic methods are an alternative to those classical procedures. Abstract : Drug bust : Currently, the most widely used methods for drug detection are based on techniques that require large measurement times, the use of sophisticated equipment, and qualified personnel. Chromo‐ and fluorogenic methods are an alternative to those classical procedures. Herein, chromo‐ and fluorogenic probes for illicit drug detection are described. AuNPs= gold nanoparticles.